Hydrotrupes chinensis Nilsson, 2003 (Coleoptera: Dytiscidae): new records, (re)description of adult and larva, and notes on its biology. Issue 3 (3rd July 2019) - Alarie, Yves; Michat, Mariano C.; Jia, Fenglong; Hájek, Jiří
Abstract: Hydrotrupes chinensis Nilsson, 2003 described from the holotype collected in Anhui Province, China, is newly recorded from three localities in Guangdong Province, ca. 750 km southwest from the type locality. The species seems to inhabit hygropetric habitats exclusively, with diurnal larvae and nocturnal adults hidden under stones or in cracks in rock during the day; when disturbed, the adults readily jumped off the rock surface. The adult is redescribed. The larvae are described and illustrated for the first time, with detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment, and urogomphi. Whereas similar morphologically to the Nearctic endemic Hydrotrupes palpalis Sharp, 1882, the first instar larva of H. chinensis distinguishes by presence of six lamellae clypeales, two additional spine-like setae both on the last abdominal segment and urogomphomere 1, and the strongly developed egg bursters.